Experimental Investigation of Diesel-WCOB Engine Performance with A Small Proportion of Ethanol/Isobutanol as A Fuel Additive - Alrubaiy, Ahmed AAG.; Aljuhashy, Radwan M.; Al-Bakri, Basim A.R. (International Journal of Integrated Engineering, 2023)
The globe is beginning to face fast-expanding global warming concerns that require immediate treatment. Biodiesel can be considered the most widely used and versatile sustainable fuel for a variety of uses. Because it is biodegradable, environmentally friendly, and renewable, it offers a viable solution to the looming energy crisis. Waste cooking oil is among the locally available sources that might be utilized as an extra source in different countries at a reasonable cost. Combining used cooking oil and diesel is a viable option for diesel engines because it has been certified for use at blending ratios as low as 20% as a commercial fuel. However, when it comes to fuel additives, the best alternative is to use waste cooking oil at high mixing ratios with diesel to power diesel engines. The goal of this research is to examine the various performance parameters of a diesel engine and the characteristics of biodiesel blended fuels by measuring the specific fuel consumption of the brakes and the thermal efficiency of the brakes and to investigate the impact of isobutane and ethanol additions at rates of 5% and 10% on the properties of the fuel and engine efficiency to enhance the specifications of the blended fuel in high proportions B40. Mixed fuel B40 with 10% ethanol (B40E10) can be used as a highly mixed fuel to enhance diesel engine performance. The density, kinematic viscosity, and flash point of diesel fuel were the lowest and rise with the amount of WCOB in the mixture, while the blended fuel B40 had the greatest value and improved with the percentage of additives. Increases in the proportion of additives also result in a visible rise in the braking force and fuel consumption.